Prevalence of pressure ulcers in Thai wheelchair users with chronic spinal cord injuries - A. Kovindha (2018)
© 2015 International Spinal Cord Society All rights reserved. Study design:A cross-sectional study.Objectives:To study prevalence of pressure ulcers (PrUs), quality of life (QoL) and effect of wheelchair cushions used by Thai wheelchair users with chronic spinal cord injury (SCI).Setting:Maharaj Hospital, Chiang Mai, Thailand.Methods:Thai chronic SCI wheelchair users, aged over 18 years and non-ambulatory with ASIA impairment scale A, B or C were recruited. They completed the PrUs questionnaire and rated the EuroQoL-5D and their health status with a visual analog scale (VAS). Demographic data of each participant were extracted from medical records. The EQ-5D health states were transformed to utility scores by using the Thai algorithm and the prevalence of PrUs was reported. The EQ-5D, the utility scores and the health status VAS were compared between those with and without current PrUs and between those participants using foam and air-filled cushions.Results:Of 129 participants, 26.4% had current PrUs at the time of the study, 27.9% had healed PrUs and 45.7% never had PrUs. The median VAS score for health status was 70 (Q1=50, Q3=80). Based on the EQ-5D, only one dimension (anxiety/depression) was significantly different between those with and those without current PrUs (P=0.015). Those using an air-filled cushions had a mean utility score four times higher than of those using a foam cushion (0.131 vs 0.032, P=0.089) but not statistically significant.Conclusions:PrUs are still prevalent among Thai wheelchair users with chronic SCI. Anxiety/depression is associated with current ulcers.